The concept of ART DÉCO - Weimer, Günter (Revista UFG, 2017)
After the political opening-up in the aftermath of the dictatorship, during which our country’s traditional architecture journals had disappeared, an intense revision of architectural concepts took place. Along with it came an extensive coining of neologisms – many of which were contradictory or even absurd – in an attempt to provide a new understanding of architectural art. The most characteristic example is the concept of “modern” which, throughout the evolution of architecture, from Vitruvius onwards, had always been understood as a synonym for “contemporary”. And it was exactly to this that architects were referring around the time of World War II, when they opposed the historicism then in vogue. They wanted to put an end to the stylistic formalism taken from historical works in order to based themselves on new concepts and minimal forms, expressive from the point of view of the industrial materials being used and up-to-date in terms of constructive techniques. (...)